Identifikasi Praktik Ecolodge di Indonesia Berdasarkan Prinsip Ekowisata: Studi Literatur - Puteri Raysa Azzahra; Nabilah Rizka E.; Ismarini Pratami P.; Nadya Karina A.; Yulistighasatil Khairiyah; Alhilal Furqan (JURNAL NASIONAL PARIWISATA, 2023)
The increase in ecotourism destinations encourages the growth of ecolodge practices, which are a form of lodging accommodation offered to tourists. As an important component of ecotourism, ecolodge practices must also comply with ecotourism principles. Therefore, the identification of ecolodge practices needs to be done to be able to assess their suitability with ecotourism principles which include nature-based, sustainability, education and research, and moral imperatives. This identification was carried out on four ecolodges under the auspices of Ecolodge Indonesia qualitatively through website searches and literature studies. The basis for the assessment used in this identification is by looking at the performance of the best ecolodges in the world, hereinafter referred to as best practices. Based on the identification results, in general the four ecolodges under Ecolodge Indonesia have implemented best practices in accordance with ecotourism principles. Even so, there are still improvements that need to be made to increase the suitability of ecolodge practices with ecotourism principles, such as the use of environmentally friendly raw materials and the transparency of profit sharing with local communities. The identification results also show that differences in social, cultural, and ecological conditions of the four ecolodges are the cause of differences in the implementation of the ecotourism principles applied.